DARE Newsletter, Vol. 4, No. 4, Fall 2001 - DARE; Goebel, George; Simon, David (Dictionary of American Regional English, 2001)
Contents: "The Story of an Entry--shuck v(2)" by George Goebel; "Funding Update" by David Simon; "Coming in Volume IV"; "Where Are They Now?: Joe Marek, Jayne Marek"; "Staff Member Profile: Karen Krause"; "Notes and Quotes"; "DARE in the News and on the Net"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Fieldwork; Lexicography; Regional English; English Language -- Dialects -- United States